Strategi Pengembangan Wisata Halal Asta Sayyid Yusuf Talango Kabupaten Sumenep - Ana Amanda Syafi’ul Ummah; Hasan, Dony Burhan Noor (Jurnal Iqtisaduna, 2023)
Halal tourism is a rapidly growing market segment, especially in countries with a majority Muslim population. However, there are still shortcomings in the development and marketing of halal tourism. The aim of this research is to find out and analyze halal tourism development strategies with GMTI GMTI (Global Muslim Travel Index) standards. Formulating a halal tourism development strategy is considered important, because the potential for halal tourism can become a source of income for local communities. By developing and strategically utilizing halal tourism attractions, it can improve the community’s economy, provide employment opportunities and encourage the growth of small businesses in tourist areas. For this reason, researchers want to examine further the strategies for developing halal tourism in Asta Sayyid Yusuf Talango in Sumenep Regency. This research is descriptive qualitative research. The research subject is the management of Asta Sayyid Yusuf. Researchers will use primary and secondary data. This research concludes that in formulating a halal tourism development strategy it is necessary to pay attention to several aspects. First, development of supporting infrastructure. Second, proper promotion and marketing to reach the halal tourism market. Third, developing tourism products and services that comply with halal principles.